1991
DOI: 10.1111/j.1464-410x.1991.tb15395.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Foreign Bodies in the Urethra and Bladder

Abstract: We report 8 cases of self-inserted unusual foreign bodies in the lower urinary tract, all being treated from 1976 to 1990. Three of them were located in the urethra and 5 in the bladder. Several objects were found (electric cable, tweezers, hairpin, drawing pin, pebbles, paper clip). In 4 cases the objects were inserted for masturbatory purposes. Five of the patients were psychologically ill or handicapped. The most common reason for consultation was dysuria, and the treatment procedures were endoscopy in 5 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 8 publications
0
37
0
5
Order By: Relevance
“…Documented objects described in urinary bladders have included batteries, wires, hair pins and screws. [1][2][3][4] A singular approach for all intravesical objects is inappropriate. Moon and colleagues found that the exact strategy for foreign body removal from the bladder is dictated by the size, location and mobility of the object.…”
Section: Discussionmentioning
confidence: 99%
“…Documented objects described in urinary bladders have included batteries, wires, hair pins and screws. [1][2][3][4] A singular approach for all intravesical objects is inappropriate. Moon and colleagues found that the exact strategy for foreign body removal from the bladder is dictated by the size, location and mobility of the object.…”
Section: Discussionmentioning
confidence: 99%
“…A low density linear object (red arrow) was seen lying obliquely in the pelvis and appeared to be aligned with the smaller foreign body hairpin, matchsticks, pen, fruit kerels, fish hooks, drinking straw, nails, rifle bullet, chew gum, snake, razor blade, wrist watch, etc [4,5]. Aetiology of foreign body in the bladder may be classified as insertion of foreign body by the person him/her self, iatrogenic (penetration during surgery of urinary tract, uterus, vagina and abdomen) or migration from adjacent organs (intrauterine devices).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the foreign body was inserted to urethra to prevent conception [5]. The duration of symptoms before diagnosis ranged from weeks to few months and the interval between insertion and removal of foreign body ranged from month to few years [4]. Complication of foreign body in lower urinary tract includes infection, abscess, extravasation, diverticuli, perforation, fistula formation and stone formation however serious life threatening complications are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases are associated with sexual stimulation, debilitation and psychiatric disorders. Self-insertion is more common in males than in females [1]. In some cases, the foreign body was inserted into the urethra to prevent conception [2].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]. Some of these foreign bodies are particularly extraordinary and bizarre including a rifle bullet, squirrel tail, chewing gum, snake, razor blade handle, wrist watch, crystal rod, and light-bulb [2,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%